Matter of trust - "West, Nigel" (London, 1985)
Was the former Director-General of the Security Service, Sir Roger Hollis, a traitor? What was the events in the 1960s which led to the self-destructive searches for Soviet 'moles'? Why was it that in more than thirty years only one KGB 'illegal' was ever found in Enlgand by MI5? Who was the defector whose memory of files in Moscow led to the identification of more than a dozen Russian spies in the West? Meticulous research backed by hundreds of hours of interviews with agents, double agents and case officers has resulted in answers to these questions. The account of Britain's premier counter-intelligence organization is thoroughly documented with names, dates and places.
Keywords: MI5 - History